I love my mommy because - Gaylord, Laurel Porter (New York : Dutton Children's Books.)
Familiar phrases from preschooler's world give a child's-eye view of being an animal baby. Many different animal mothers are show caring for their young.
Keywords: Mother and child -- Fiction